Innovation Snowballing and Climate Law - Zachary Liscow; Quentin Karpilow (Washington University Law Review, 2017)
Findings at the frontier of economics suggest startling implications of an under-appreciated fact about technological development: innovation builds on itself, developing path dependencies in which past innovations attract similar, but more advanced, innovations. Innovation snowballs. The world economy needs to undergo a dramatic transformation to avoid the risk of catastrophic effects from climate change. Policy to encourage this transformation should be sensitive to innovation snowballing. The conventional policy view has long been that, to address a social harm like pollution, the right response is simply to tax the behavior causing the harm, leading to a variety of responses including induced technological change. The Article shows that this view is incomplete. Rather, the most efficient response to climate change—and likely other social harms—requires a combination of taxes and a big push of government support to specifically redirect innovation toward technologies that alleviate social harm. Without a big push in cleantech innovation to change the trajectory of innovation, energy technology will tend to stay trapped in its high-pollution path. For climate policy and likely other pressing policy issues, the Article suggests a paradigm shift in the role of innovation policy: from broad to targeted. Otherwise, the transition to clean energy will be longer, more expensive, and riskier for the global climate. The Article shows how to efficiently deploy innovation policy to meet this challenge.
Keywords: cleantech; innovation snowball; energy technology; technological development; climate change; climate change solution